Languaging waste in public: a participatory exhibit on curbside gleaning - Crispin Thurlow; Laura Wohlgemuth; Alessandro Pellanda; Charmaine Kong (Frontiers in Communication, 2026)
This Community Case Study documents a participatory exhibit designed to explore how everyday waste practices are organized and evaluated in language. Developed as part of our larger Articulating Rubbish project, the exhibit focused on curbside gleaning: the informal, technically illegal practice of leaving unwanted items outside one's home for others to take. Combining a large-scale visual montage with two interactive displays, the exhibit presented our research to members of the wider public while creating a dialogical space for them to reflect on their own and others’ discarding practices. The case study highlights the value of a “messy” methods approach – including guerilla ethnography and montage – for surfacing the link between language and waste.